E-Collaborative Learning Synergy: Exploring Peer Interaction and English Proficiency in Virtual Collaborative Classrooms - Harun, Halipah; Abdullah, Muhammad Kamarul Kabilan (Jurnal Pendidikan Bitara UPSI, 2024)
E-Collaborative learning (ECL) is revolutionizing language education by harnessing digital platforms to enrich peer interaction and elevate English proficiency. This comprehensive literature review addresses the urgent necessity to consolidate findings on the effectiveness of ECL and its significant integration into pedagogy in educational environments. Through adherence to PRISMA guidelines, the study scrutinized 25 peer-reviewed articles published between 2019 and 2024, unearthing four fundamental themes: (1) Online Learning and Engagement, (2) Language Proficiency and Learning Outcomes, (3) Multimodal and Intercultural Communication, and (4) Student Attitudes and Self-Efficacy. The results unravel the intricate interplay of technology, pedagogy, and human factors in shaping language acquisition outcomes. ECL gives prominence to the demand for tailored ECL strategies and charts a course for future research, including longitudinal studies on the enduring effects of ECL and the creation of standardized assessment tools for collaborative online learning environments. The analysis delves into the potential of ECL to bridge cultural gaps and cultivate global communication skills, addressing the evolving requirements of language learners in an increasingly interconnected world. This exhaustive analysis imparts invaluable insights for educators and researchers, propelling the move towards more effective ECL implementation in language education and contributing to the progress of digital literacy in the field.